A Commentary: The Position of Ethnic Minorities From the Connection Between Theory of Justice and Good Governance. (January 2022) - Marwan, Awaludin
Ethnic minorities are sometimes presented as "outsiders, " "awkward, " "alien, " and many other pejoratives by the "leviathan of majority". This article will theoretically analyze how ethnic minorities struggle to pursue justice and access their right to good governance. Rawls's theory of justice simply seems as the support of "majorities" sense of justice, which disregards the sense of justice by minority. Because of the color of their skin, language, cultural identities, and national origin, ethnic minorities are trapped under the battle of power holders that can be explained by the notion of biopolitics. Biopolitics is a method of investigating the interconnection between human body and power relation. Furthermore, the position of ethnic minorities in these power battles is appeared such homo sacer. Homo sacer is one who has been condemned and may be killed by anybody in a figure of Roman law. The concept of homo sacer can be used to explain the position of ethnic minorities who have always been victimized. In addition, to establish a concrete example of a case about problems faced by ethnic minorities, I will discuss the protection of ethnic minorities through the framework of law and democracy in Indonesia and the Netherlands.